Association between Low blood lead levels and increased risk of dental caries in children: a cross-sectional study. Issue 1 (December 2017) - Kim, Young-Suk; Ha, Mina; Kwon, Ho-Jang; Kim, Hae-Young; Choi, Youn-Hee
Abstract Background The objective of this study was to examine the association between low blood lead levels of <5 μg/dL and the development of dental caries among children. Methods The Children's Health and Environment Research (CHEER) group recruited a cohort of 7, 059 school-aged children from six Korean cities. The final study populations in the permanent and deciduous teeth groups were 1, 564 and 1, 241 children, respectively, after excluding 4 children with blood lead levels of >5 μg/dL. Compared with the children who did not have dental caries, the risk of having dental caries according to blood lead level was estimated by using the zero-inflated negative binomial model. Results The geometric mean (geometric standard deviation, maximum) blood lead level was 1.53 μg/dL (1.57, 4.89 μg/dL), and 74.4% of children had a level of <2 μg/dL. Blood lead level was significantly higher in the children with than in those without deciduous dental caries (1.59 vs. 1.51 μg/dL), similarly with permanent dental caries (1.65 vs. 1.51 μg/dL). After adjustment for covariates, deciduous teeth surfaces that were decayed and filled increased significantly with increasing blood lead levels in a dose-dependent manner (prevalence ratio, 1.14; 95% confidence interval: 1.02–1.27). However, the risk of having dental caries in permanent teeth was not linearly associated with the increase in blood lead level. Conclusions In the sum of decayed and filled surfaces, we found a significant increase in risk of dental caries of the deciduous teeth with an increase in blood lead levels (<5 μg/dL) but found no statistical significance in the association with decayed and filled surfaces of caries separately.